2018
DOI: 10.1002/hbm.24487
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length as a predictor of emotional processing in the brain

Abstract: Shorter telomere length (TL) has been associated with the development of mood disorders as well as abnormalities in brain morphology. However, so far, no studies have considered the role TL may have on brain function during tasks relevant to mood disorders. In this study, we examine the relationship between TL and functional brain activation and connectivity, while participants (n = 112) perform a functional magnetic resonance imaging (fMRI) facial affect recognition task. Additionally, because variation in TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 84 publications
1
13
0
Order By: Relevance
“…This result supports the hypothesis that TL might represent a marker of hippocampal vulnerability, as previously suggested [62]. A subsequent study further explored the association between peripheral TL and functional brain activation and connectivity, in a sample comprising patients with BD and first-degree relatives, as well as healthy volunteers [63]. TL was positively associated with increased face-related activation in the amygdala, during a task in which participants were asked to identify facial emotions.…”
Section: Telomeres and Mood Disorderssupporting
confidence: 83%
See 1 more Smart Citation
“…This result supports the hypothesis that TL might represent a marker of hippocampal vulnerability, as previously suggested [62]. A subsequent study further explored the association between peripheral TL and functional brain activation and connectivity, in a sample comprising patients with BD and first-degree relatives, as well as healthy volunteers [63]. TL was positively associated with increased face-related activation in the amygdala, during a task in which participants were asked to identify facial emotions.…”
Section: Telomeres and Mood Disorderssupporting
confidence: 83%
“…This association was observed, regardless of the diagnosis status. Furthermore, a polygenic risk score for TL was positively associated with medial prefrontal cortex activation [63]. These results support the existence of a link between TL and emotional brain activity.…”
Section: Telomeres and Mood Disordersmentioning
confidence: 64%
“…A recent experimental study found that longer buccal telomere length was associated with activation in the amygdala and cuneus region of the brain related to an emotional cue, suggesting that telomere length predicts emotional brain activity and connectivity ( 41 ). Longer telomere length could be a crude proxy for a greater potential for learning.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of psychiatry, meta-analyses reveal that, in general, psychiatric disorder patients exhibit shorter leukocyte telomere lengths relative to unaffected individuals of equivalent ages, which could contribute to the increased burden of age-related disease [21][22][23][24]. In addition to shorter telomere lengths, psychiatric disorder patients frequently exhibit neurological differences such as smaller hippocampi [25][26][27], and some studies have suggested a relationship between shortened telomere length and psychiatric disorder neuropathology [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%